Analysis of Student Perceptions of Project-Based Learning: A Case Study in Experimental Physics Course - Sutrio, Sutrio; Gunawan, Gunawan; Hikmawati, Hikmawati; Verawati, Ni Nyoman Sri Putu; Busyairi, Ahmad; Haslinda, Padia; Isnaini, Ahmad Hardyan (Department of Physics Education, Universitas Mataram, 2025)
The urgency of this research lies in the critical need to understand the effectiveness of Project-Based Learning (PjBL) within the context of the Experimental Physics course, particularly in responding to modern curricular demands that emphasize problem-solving and creativity. This study aims to analyze student perceptions of PjBL implementation, covering learning style profiles, learning experiences, challenges, support systems, and the impact on problem-solving abilities. Utilizing a quantitative approach with a descriptive design, data were collected through surveys administered to students enrolled in the Experimental Physics course. The results indicate that the majority of students (65.7%) possess a Kinesthetic learning style, which aligns strongly with PjBL characteristics that emphasize hands-on practical activities. Student perceptions were classified as highly positive, with the highest ratings observed in the aspects of enhanced creativity and the relevance of projects to real-world applications. An interesting finding highlights the presence of